Cicerón y la imagen del "buen gobierno" en el Renacimiento español: El Relox de Príncipes de Antonio de Guevara - Hidalgo de la Vega, M.J.; Pérez Sánchez, D.; Rodríguez Gervás, M. (Ciceroniana On Line, 2015)
.